Explore Room(xR): Explore Digital Hotel Bedrooms Using Augmented Reality: Explore Room(xR): Jelajah Kamar Hotel Digital Menggunakan Augmented Reality - Putra, Dicky Andrey Cholisyah; Taurusta, Cindy (Universitas Muhammadiyah Sidoarjo, 2023)
xR(Explore Room) is an application feature to explore virtual hotel rooms using Augmented Reality. By utilizing Augmented Reality technology, users will be able to ensure the hotel services which will be obtained before booking hotel room. The application feature is developed using the Agile Development method, which is software development method that requires quick adjustments and is able to receive changes repeatedly and oriented towards the quality of the results developed. xR(Explore Room) operates AR technology as the main technology where the feature will display a 3-dimensional model of a hotel room using markers on the phone screens. From use of the Agile method, it is found that the application feature which made requires several improvement for the results to be maximized. The results of application testing suggest adding human resources to produce more 3D room model assets to adjust number of rooms that have been registered in the application.